Wind engineering study of atmospheric dispersion of airborne materials released from a floating nuclear power plant - Meroney, Robert N., author; Cermak, Jack E., author; Connell, J. R., author; Garrison, James A., author; Fluid Dynamics and Diffusion Laboratory, Department of Civil Engineering, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1974)
Measurements were made in the meteorological wind tunnel of the concentration of gas at selected sampling ports on a 1:450 scale model for selected emission locations on and at the sea surface upwind of the model of a floating nuclear power plant complex including the breakwater. The data obtained include time exposure, still photographs and color motion pictures of smoke from the selected sources. Maps of non-dimensional concentrations at sampling points on the plant are supplemented by tables of the vertical distribution of non-dimensional concentrations at a selected location. The effects of wind direction, source emission rate and effluent initial buoyancy are evaluated for both neutral and stable density stratification. The effect of doubling the height of the plant vent stack and, in neutral stratification, the effect of changing the height of the breakwater and wind speed were also evaluated. The results indicate that 1. Wind direction strongly alters the pollutant transport pattern. 2. Increasing the plant vent stack emission rate to well above that of a leak to, say, Vs /V a = 3 greatly reduces the concentration at the selected sampling points. 3. Doubling the height of the plant vent stack is quite effective in reducing concentrations at the sampling points especially in stable stratification. 4. Upwind sea surface point sources of pollutant are for the most part deflected laterally around the breakwater in stable stratification with negative buoyancy of the source. However, a small amount of elevation of source material (by positive initial buoyancy or otherwise) can alter this picture somewhat to allow a rather wide distribution within the complex. 5. The contaminant vessel leak pollutant is strongly entrained into leeside parts of plant components, plant and plant complex for most wind directions. 6. It will be difficult to select an intake point on the plant, which can assuredly be free of pollutant from low flow rates out of the original height plant vent stack. The data, however, does permit the selection of a most preferable location, which will minimize filter loads.
CER74-75RNM-JEC-JRC-JAG4.
August 1974.
Keywords: Nuclear facilities -- United States; Turbulent diffusion (Meteorology); Atmospheric diffusion